DEPRESSION IN ELDERLY PATIENTS WITH LOW VISION: IMPLICATIONS FOR MENTAL HEALTH AND FUNCTIONAL OUTCOMES (Journal of Medical & Health Sciences Review, 2026)
AIMS AND OBJECTIVES: To determine the effect of depression in the adults patients suffering from low vision and correlation of depression with low vision.METHOD: A cross-sectional study was performed on 86 subjects who visited Low Vision Center at Mayo Hospital Lahore to determine effect of depression in adults on functioning, and daily life activities in low vision patients. All the patients were asked to fill the questionnaire so that the extent to which the quality of life is affected can be measured. Qualitative data was analyzed through frequency and percentage. This study was conducted in February, March, April and May 2022.RESULTS: Total of 86 subjects participated. Out of 86 low vision patients, 17(19.8%) none of the time, 43(50.0%) some of the time, 24(27.9%) moderate amount of time and 2(2.3%) most of the time were bothered by things that usually don’t bother them, out of 86 low vision pateints, 27(31.4%) none of the time, 25(29.1%) some of the time, 20(23.3%) moderate amount of time and 14(16.3%) most of the time were felt that just as good as other people, out of 86 low vision patients, 5(5.8%) none of the time, 43(50.0%) some of the time, 35(40.7%) moderate amount of time and 3(3.5%) most of the time felt depressed. out of 86 low vision patients, 20(23.26%) none of the time, 30(34.88%) some of the time, 18(20.93%) moderate amount of time and 18(20.93%) most of the time were happy. out of 86 low vision patients, 3(3.49%) none of the time, 28(32.56%) some of the time, 34(39.53%) moderate amount of time and 21(24.42%) most of the time were felt people were unfriendly. out of 86 low vision patients, 27(31.40%) none of the time, 25(29.07%) some of the time, 20(23.26%) moderate amount of time and 14(16.28%) most of the time were enjoyed life. out of 86 low vision patients, 22(25.58%) none of the time, 16(18.60%) some of the time, 29(33.72%) moderate amount of time and 19(22.09%) most of the time were felt sad.CONCLUSION: There were high chances in low vision patients to develop depression because of visual loss, functional impairment, and difficulty in daily life activities. Visual impairment restricted a persons’ independence, and worsened the quality of life. During the study it was possible to describe the specific indications of depression in each low vision individual. If a person is counseled properly, it is beneficial in increasing the functional performance and will also help him to avoid developing depression.